New adsorbting moisture buffer for preserving library, archive and museum materials - J. I. Aristov; I. S. Glaznev; V. N. Alekseev; L. G. Gordeeva; I. V. Salnikova; I. A. Shilova; L. P. Kundo; B. S. Elepov (Библиосфера)
A new adsorbent for maintaining air relative moisture in show-cases, boxes for deposits and containers for trans-porting library, museum and archive values is described. The results of testing this material in SPSTL SB RAS and the Institute of archeology and ethnography of RAS are discussed.